2019
DOI: 10.1042/bcj20190779
|View full text |Cite
|
Sign up to set email alerts
|

Desolvation of the substrate-binding protein TauA dictates ligand specificity for the alkanesulfonate ABC importer TauABC

Abstract: Under limiting sulfur availability, bacteria can assimilate sulfur from alkanesulfonates. Bacteria utilize ATP-binding cassette (ABC) transporters to internalise them for further processing to release sulfur. In gram-negative bacteria the TauABC and SsuABC ensure internalization, although, these two systems have common substrates, the former has been characterized as a taurine specific system. TauA and SsuA are substrate-binding proteins (SBPs) that bind and bring the alkanesulfonates to the ABC importer for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 28 publications
2
17
0
Order By: Relevance
“…A G244F substitution mutant of EgtU binds ET ≈100-fold more weakly than wild-type EgtU SBD, with strongly perturbed thermodynamics (Fig. 3b); consistent with an important role of these water molecules in organizing the ET binding site, a finding previously observed in some other QAC-specific SBPs 67,70 . Two other substitutions that target conserved residues Y419 and F293 give rise to somewhat smaller perturbations of the binding energetics and affinity.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…A G244F substitution mutant of EgtU binds ET ≈100-fold more weakly than wild-type EgtU SBD, with strongly perturbed thermodynamics (Fig. 3b); consistent with an important role of these water molecules in organizing the ET binding site, a finding previously observed in some other QAC-specific SBPs 67,70 . Two other substitutions that target conserved residues Y419 and F293 give rise to somewhat smaller perturbations of the binding energetics and affinity.…”
Section: Resultssupporting
confidence: 86%
“…3a, Table 1). These thermodynamic parameters are similar to those previously found for a taurine-specific SBP 70 , with an enthalpic driving force consistent with trimethylamine cation-π interactions found in osmoprotectant SBP-ligand complexes 60,62 . A G244F substitution mutant of EgtU binds ET ≈100-fold more weakly than wild-type EgtU SBD, with strongly perturbed thermodynamics (Fig.…”
Section: Resultssupporting
confidence: 85%
“…We next studied whether sulfonate binding pockets were conserved across SmoF homologues as well as other sulfonate-targeting solute binding proteins. Thus, we included SsuA from E. coli and Xanthomonas citri ( Beale et al., 2010 ; Tófoli De Araújo et al., 2013 ) and the taurine-binding protein TauA from E. coli ( Qu et al., 2019 ), which are solute-binding proteins associated with ABC transporters that bind assorted alkanesulfonates. We also included MalE as a well-characterized SBP that binds a non-sulfonated ligand.…”
Section: Resultsmentioning
confidence: 99%
“…Methyl Orange and Ponceau S Red are sulfonated reactive dyes whose degradation products include sulfonated and unsulfonated aromatic amines, which are an important group of environmental pollutants that are toxic in nature. 46,47 Our study identified the compounds by GC−MS: N,Ndimethylbenzyl-1,4-diamine, sulfonamide, 1,4-diaminobenzene, 2,5-diaminobenzenesulfonic acid, and 1-amino-2 naphthol as intermediates in the degradation pathway of both dyes, which are not only highly toxic as it is evidenced in Table 2 but also able to be converted through metabolic activation into mutagenic, carcinogenic, and/ or teratogenic species as is indicated by Qu et al 48 Franconibacter sp., 1MS could be inhibited by these intermediaries and not finish the detoxification, indicating that degradation products were still toxic in some cases of the original dye as emphasized by Rawat et al 49 and Bergsten-Torralba et al 50 According to Kalyani et al, 51 it is of great concern to evaluate the phytotoxicity and microbial toxicity of the dye before and after degradation, given the use of untreated and treated textile effluents that are reported in the agricultural area, and its direct impact on soil fertility. Furthermore, effluents from untreated textiles can cause serious health and environmental risks.…”
Section: ■ Results and Discussionmentioning
confidence: 82%
“…Decolorization Assay. Dye decolorization was studied using the one-factor optimization approach: The influence of various culture conditions such as pH (3, 5, 7, 9, and 11), temperature (20,37,40,45, and 50 °C), the time of incubation (24,48,72,96, and 120 h), and concentration (50, 100, 200, 300, 400, 500, 600, 800, and 1000 mg/L) of dyes on the rate of decolorization was studied. When investigating one of these factors, all others were kept constant.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%